Indonesian Government Policy Regarding Working Hours for Indonesian Female Migrant Workers Abroad in the COVID-19 Pandemic Era - Rosalinda, Henny; Hadi, Rany Purnama; Andini, Amalia Nur (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
Indonesia has been sending migrant workers since the 1970s and it is mostly dominated by women who work in the informal and low-skilled sectors such as domestic workers, child and elderly caretakers, or factory workers. The economic issue has become the biggest driving factor for these workers to work abroad, in addition to social and cultural factors. During the COVID-19 pandemic, migrant women experienced significant impacts, especially changes to increasingly longer working hours. This research aims to identify COVID-19 on Indonesian female migrant workers and produce policy recommendations that protect women's work rights. This research design is qualitative research with data collection methods through literature study and in-depth interviews with Indonesian female migrant workers abroad. Based on research results, during the pandemic many Indonesian migrant workers worked longer than the applicable standard working hours, approximately more than 15 hours per day. However, there are no clear rules or forms of protection that guarantee the welfare of Indonesian migrant workers by increasing working hours beyond the established standards.